Advances in Genetic Polymorphism Research in Rosacea: Mechanisms and Clinical Implications - Wang Z; Zhang Z (Clinical, Cosmetic and Investigational Dermatology)
Zhuangyi Wang, Zhengzhong Zhang Department of Dermatology, Affiliated Hospital of North Sichuan Medical College, Nanchong, Sichuan Province, People’s Republic of ChinaCorrespondence: Zhengzhong Zhang, Department of Dermatology, Affiliated Hospital of North Sichuan Medical College, No. 1 Maoyuan South Road, Shunqing District, Nanchong City, Sichuan Province, 637000, People’s Republic of China, Tel +8618080339898, Email laowaiaeo@163.comAbstract: Rosacea is a chronic inflammatory skin disease primarily affecting the central region of the face. Typical manifestations include erythema, papules, or pustules on the cheeks, glabella, chin, and nose, with some patients experiencing ocular involvement. The pathogenesis of this disease is influenced by both polygenic inheritance and environmental factors, with abnormalities in innate immunity and neurovascular regulation playing a leading role. Recent genetic studies have identified several key genes, including Human Leukocyte Antigen (HLA), Toll-Like Receptor 2 (TLR2), Interleukin-17 (IL-17), Cathelicidin Antimicrobial Peptide (CAMP), and others, that are closely associated with rosacea onset and progression. This review summarized recent advances in rosacea-related genetic researches, aiming to reveal the genetic basis of the disease and provide support for early intervention and precision management of high-risk populations.Keywords: Rosacea, susceptibility genes, gene polymorphism, genetic variants, genetics